INTERPRETATION OF THE NOVEL GOETZ AND MEYER BY DAVID ALBAHARI FROM THE PERSPECTIVE OF HOLOCAUST EDUCATION - Гордана М. Тодорић (Metodički Vidici, 2012)
By reading Albahari’s novel Goetz and Meyer, students are able to gain insight into the attribute of the postmodern Serbian literature. They also learn about the Holocaust (victims, perpetrators, concentration camps). Stimulating the objective observer`s point of view, the writter describes how Goetz and Meyer drive a gas-van every day from a concentration camp outside the Semlin Judenlager to the scaffold Jajunci. Writing in two different time planes, wartime as a past and the narrator`s present time, Albahari at several points clearly stresses that he is undertaking a reconstruction in order to learn more about his family that has almost completely disappeared in the Holocaust. Writing against the traditional historical method that ignores individuals for the sake of scientific objectivity, Albahari uses adventures of the two gas–van drivers as the background to discern the individual faces of the victims, but of the perpetrators too.